Discourse on National Identity in Moldovan Politics after 2009 - Oleksy, Piotr (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
Throughout the 20 years of independence, different concepts of a Moldovan nation have competed in public, scientific, and political discourse. A turning point came in 2009, when the ruling Communist Party of Moldova was replaced by a pro-European coalition of self-styled lib¬eral-democratic parties who brought about a significant pluralisation of Moldovan public life. The goal of this article is to analyse the discourse on national identity in Moldovan politics since 2009.

W ciągu dwudziestu lat niepodległości w publicznej, naukowej i politycznej dyskusji dało się zauważyć rozmaite koncepcje odnoszące się do idei narodu mołdawskiego. Punktem zwrot¬nym stało się zwycięstwo pro-europejskiej koalicji partii liberalno-demokratycznych w 2009 r., co doprowadziło do pluralizacji życia publicznego w Mołdawii. Celem artykułu jest analiza dys¬kursu tożsamościowego w mołdawskiej polityce po 2009 r.
Dyskurs tożsamościowy w mołdawskiej polityce po roku 2009